Effects of Glucose Load and Nateglinide Intervention on Endothelial Function and Oxidative Stress - Leilei Wang; Lixin Guo; Lina Zhang; Yan Zhou; Qinghua He; Zheng Zhang; Meng Wang (Journal of Diabetes Research)
We analysed endothelial function and oxidative stress in patients with abnormal glucose metabolism, the effect of glucose load, and the impact of nateglinide. 109 participants were grouped into newly diagnosed diabetes, prediabetes, and control. Fasting plasma glucose (FPG), postprandial plasma glucose (PPG), glycosylated haemoglobin (HbA1c), and glycated albumin (GA) varied significantly among the study groups (P<0.01). Nitric oxide (NO) and insulin resistance index (HOMA-IRI) levels were markedly different between the newly diagnosed diabetes and the control (P<0.01). Glucose loading lowered flow-mediated endothelium-dependent dilation (FMEDD), NO, and superoxide dismutase (SOD) (P<0.01). Fasting and glucose loading FMEDD, FPG, PPG, HbA1c, and GA were negatively correlated (r=-0.4573, −0.4602, −0.3895, −0.3897, and r=-0.4594, −0.4803, −0.4494, −0.3885; P<0.01), whereas NO, SOD, and HOMA-β were positively correlated (r=0.2983, 0.3211, 0.311, and r=0.1954, 0.361, 0.2569; P<0.05). After the treatment with nateglinide, significant decreases in FPG, PPG, GA, HbA1C, endothelin-1(ET-1), malondialdehyde (MDA), and HOMA-IRI were observed, whereas FMEDD, NO, and SOD increased (P<0.01). Thus, the study demonstrated the adverse effect of glucose load on endothelial function and oxidative stress. Nateglinide lowers blood glucose, reduces insulin resistance and oxidative stress, and improves endothelial function in newly diagnosed diabetes.